CONTEMPORARY PSYCHOPHTHALMOLOGY: INTERFACES BETWEEN THE MIND, THE EYE AND COMPREHENSIVE CARE: AN INTEGRATIVE NARRATIVE REVIEW (Editora Impacto Científico, 2025)
Psycho-ophthalmology is an emerging interdisciplinary field integrating ophthalmology, psychiatry, and neurosciences. This chapter discusses its historical evolution, neuropsychological foundations, and biomolecular evidence supporting the interrelationship between mental phenomena and ocular disorders. Based on an integrative literature review — including Kaplan and Milder (1961), Bruscolini et al. (2023), Vasanthakumar et al. (2024), and Souza-Silva et al. (2019; 2020; 2023) — the chapter explores the psychobiological dimension of vision and its impact on human behavior, as well as parental stress in contexts of childhood blindness. The interdisciplinary approach reinforces the need for medical education that recognizes the eye as a biological, psychological, and social organ.DOI: https://doi.org/10.56238/edimpacto2025.091-023